Prevalence and Factors Associated with Syphilis among Mothers with Missed Opportunities for Antenatal Syphilis Testing in Rural Western Uganda: A Cross-Sectional Study - Theoneste Hakizimana; Joy Muhumuza; Fabrice Molen Selamo; Marie Pascaline Sabine Ishimwe; Rogers Kajabwangu; Osman Mohamud Jelle; Joshua Muhumuza; Sonye Magugu Kiyaka; Sandra Nyakato; Yarine Fajardo (Hindawi Limited, 2023)
Background. Early prenatal syphilis testing and treatment are essential preventative measures for maternal syphilis and associated adverse pregnancy outcomes of pregnancy; however, data shows that two-thirds of all cases are missed among women who visit prenatal care center at least once but are not tested for syphilis. This study determined the prevalence and factors associated with syphilis infection among mothers with missed opportunities for antenatal syphilis testing in rural western Uganda delivered at Fort Portal Regional Referral Hospital (FRRH). Methods. A cross-sectional study was done during the period from April 2022 to June 2022. A total of 124 participants had been recruited consecutively from postnatal ward of FRRH. Pretested questionnaires were used to obtain information on data required for analysis. Venous blood sampling (2 ml taken from the forearm using anticoagulant free vacutainer) was done for all mothers who missed opportunity for prenatal syphilis testing using both RPR and TPHA. Descriptive statistics followed by binary logistic regression analysis was done using SPSS version 22.0. Results. The prevalence of syphilis infection was 27 (21.8%). After adjusted analysis, having more than one sexual partners in the past one year was associated with higher odds of syphilis infection (aOR=24.922, 95% CI: 4.462-139.201, p<0.001), and staying with the partner was found to be associated with lower odds of syphilis infection (aOR=0.213, 95% CI: 0.040-1.142, p=0.050). Conclusions. The study identified high prevalence of syphilis infection among mothers with missed opportunities for antenatal syphilis testing, and this was positively associated with having more than one sexual partners in the past one year and negatively associated with not staying with partner.